2020
DOI: 10.3389/fmars.2019.00794
|View full text |Cite
|
Sign up to set email alerts
|

Sperm Motility Impairment in Free Spawning Invertebrates Under Near-Future Level of Ocean Acidification: Uncovering the Mechanism

Abstract: Ocean acidification (OA) refers to the decrease in ocean water pH resulting from the increasing absorption of atmospheric CO 2. This will cause changes in the ocean's carbonate chemistry system with a resulting impact on reproduction of marine organisms. Reproduction is the fundamental process that allows the conservation of the species; in free-spawning marine invertebrates, this process is highly sensitive to changes in seawater quality and chemistry. To date, the majority of the studies concerned OA effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 67 publications
0
17
0
Order By: Relevance
“…It is possible that regulation of mitochondrial output via sAC-PKA signaling in invertebrate sperm is an additional means of “tuning” flagellar motility. Importantly, because mitochondrial function and sperm motility are both impaired under simulated ocean acidification in sea urchin, mussel, and ascidian sperm ( 21 , 67 ), a description of the molecular mechanisms underlying sperm motility and their response to environmental conditions is critical for predicting the susceptibility of reproduction to climate change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that regulation of mitochondrial output via sAC-PKA signaling in invertebrate sperm is an additional means of “tuning” flagellar motility. Importantly, because mitochondrial function and sperm motility are both impaired under simulated ocean acidification in sea urchin, mussel, and ascidian sperm ( 21 , 67 ), a description of the molecular mechanisms underlying sperm motility and their response to environmental conditions is critical for predicting the susceptibility of reproduction to climate change.…”
Section: Discussionmentioning
confidence: 99%
“…Sperm in particular are acutely susceptible to environmental disturbances due to their small size and brief lifespan (13), and climate change stressors including ocean warming and acidification have reduced coral sperm production (11,14), motility (10,15,16), and fertilization success (17,18) in several species. The mechanisms driving these declines in sperm performance are unknown, but both warming and acidification may disrupt coral cellular metabolism and acidify the cytosol (19)(20)(21), two processes that are important for sperm motility in other species (22). Indeed, initial evidence indicates that alkalinization of coral sperm cytosol promotes motility (23), highlighting the importance of understanding the Significance Reef-building corals are the keystone species of the world's most biodiverse yet threatened marine ecosystems.…”
mentioning
confidence: 99%
“…Although the influence of sAC activity on sperm mitochondrial function remains unexplored, it is possible that regulation of mitochondrial output via sAC is an additional means of "tuning" flagellar motility. Importantly, because mitochondrial function and sperm motility are both impaired under simulated ocean acidification in sea urchin, mussel, and ascidian sperm (21,61), a description of the molecular mechanisms underlying sperm motility and their response to environmental conditions are critical for predicting the susceptibility of reproduction to climate change.…”
Section: Soluble Adenylyl Cyclase May Play a Central Role In Coral Sperm Physiologymentioning
confidence: 99%
“…Sperm, in particular, are an acutely susceptible life stage to environmental disturbances due to their small size and brief life span (13), and climate change stressors including ocean warming and acidification have reduced coral sperm production (11,14), motility (10,15,16) and fertilization success (17,18). The mechanisms driving these declines in sperm performance are unknown, but both warming and acidification may disrupt coral cellular metabolism and acidify the cytosol (19)(20)(21), two processes that are important for sperm motility in other species (22). Indeed, initial evidence indicates that alkalinization of coral sperm cytosol promotes motility (23), highlighting the importance of understanding the molecular pathways that connect pH-dependent signaling with changes in cellular performance.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, the effects of OA in combination with aquatic pollutants on gametes are still poorly studied. Nonetheless, it was observed that significant and persistent changes in environmental variables, such as pH, might affect the normal reproductive success of different marine species including bivalves [31][32][33], sea urchins [34][35][36][37][38], corals [39][40][41], polychaetes [28,42], and also fish [43]. Marine broadcast spawners, such as echinoderms, might be particularly susceptible to OA and pollutants because of their reproductive strategy.…”
Section: Introductionmentioning
confidence: 99%